ANALISIS HUKUM PENGGUNAAN PEWARNA KARMIN (TELAAH ATAS FATWA MUI DAN LAJNAH BAHTSUL MASA’IL NU) - Lintang Ramadhani; Rofianti Anggraini; Rahmad Agus Hartanto; Riavita Maghfiroh; Muhammad Asrori (An Natiq, 2024)
Carmine coloring is a type of food coloring that is used to increase the attractiveness of food. This dye produces red and its derivatives. Apart from being used in food, this dye is also often found in beauty products. However, this carmine dye has sparked controversy among Muslims, this controversy is motivated by differences of opinion in determining the law on its use. Among them are legal contradictions issued by Majelis Ulama Indonesia and Lajnah Bahtsul Masa'il Nahdlatul Ulama. Therefore, this research is here to discuss several main things, first is to find out the legal procedures between Majelis Ulama Indonesia and Lajnah Bahtsul Masa'il Nahdlatul Ulama, second is to find out the legal product for the use of carmine dye from Majelis Ulama Indonesia and Lajnah Bahtsul Masa 'il Nahdlatul Ulama. This research uses qualitative research methods with pure library research as the data source. As a result, the law for using carmine dye according to Majelis Ulama Indonesia is halal, in contrast to the Lajnah Bahtsul Masa'il Nahdlatul Ulama which stipulates that the use of this dye is haram.